RESEARCH METHODOLOGY OF PEDAGOGICAL CONDITIONS OF COSCIOUS ATTITUDE FORMATION TO THE STUDY OF THE FUTURE OFFICERS OF THE NATIONAL GUARD OF UKRAINE - Луценко, Олена Володимирівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
This article analyzes the results of the pedagogical conditions’ methodology of a conscious attitude formation to study of the future officers. The author’s definition of the key concept of «Pedagogical conditions of formation of the future officers of the National Guard of Ukraine conscientious attitude to study» is given. It was found that the method of study has binary-dialectical character. The specifics of the pedagogical environment at the level of the individual institution, which is undertaken to prepare future officers of the National Guard of Ukraine has also been investigated. Structural analysis of the pedagogical conditions of activity of higher education institutions was carried out with the specific conditions of learning, as well as the specific higher educational institution has been found and the main components of the system were emphasized